Assessment of the levels of polycyclic aromatic hydrocarbons(PAHs) in sediments and water from Mokolo and Blood rivers of the Limpopo Province, South Africa - Mogashane, Tumelo Monty (My University, 2017)
The presence of polycyclic aromatic hydrocarbons (PAHs) in the environment is of major concern since these compounds are highly persistent, toxic and wide spread pollutants. The aim of this study was to evaluate the levels of PAHs in water and sediment samples collected from Blood and Mokolo Rivers in Limpopo Province, South Africa. Liquid-liquid extraction (LLE) was used for the extraction of PAHs from water, whereas PAHs in sediments were extracted using optimised microwaveassisted extraction (MAE). Furthermore, ultrasonication and a combination of ultrasonication and mechanical agitation were used for the extraction of PAHs from sediments samples. The quantification of sixteen (16) PAHs in water and sediment was carried out using gas chromatography-mass spectrometry (GC-MS) in selected ion monitoring (SIM) mode and by GC-flame ionisation detector (GC-FID). Concentrations of PAHs in sediments were higher than in water. The highest concentrations of PAHs were obtained in Mokolo River sediments, with the concentration ranging between 0.044 and 51.9 mg/kg. The levels of PAHs recorded in Blood River sediments were lower than those obtained in Mokolo River with concentrations ranging between 0.014 and 3.10 mg/kg. In water samples, higher levels of PAHs were observed in Mokolo River (between 0.0219 and 1.53 µg/L) while lower concentrations were recorded in Blood River (between 0.0121 and 0.433 µg/L). In water and sediment samples from both Rivers, higher molecular weight (HMW) PAH compounds (4-6 rings) were found at greater concentration levels than lower molecular weight (LMW) PAHs (2-3 rings), and this can be attributed to pyrogenic activities in the study areas. The efficiencies and accuracy of the methods for the extraction of PAHs were determined by assessing the recoveries of samples spiked with known amount of standards (for water samples), while a certified reference material (CRM) was used for sediments. Percentage recoveries ranged from 67.6 to 115% for LLE and 83.8 to 125% for MAE for both sample types. Diagnostic ratio was used for the source identification of PAHs in sediment samples. Several PAHs ratios indicated that both pyrogenic and petrogenic could be the sources of these compounds in both rivers. Toxic equivalency factors (TEFs) and benzo(a)pyrene equivalent (BaPE) were used to quantitatively estimate the PAHs potential human health risk. The assessment of ecotoxicological risk indicated that the v sediment samples collected from Mokolo River are at high toxicity risk while sediments from Blood River are at low sediment toxicity risk.
Thesis (M.Sc. (Chemistry)) --University of Limpopo, 2017
Keywords: Polycyclic aromatic hydrocarbons (PAHs); Liquid-liquid extraction (LLE); Microwave assisted extraction (MAE); Polycyclic aromatic hydrocarbons